What does extinction have to do with confabulation?. (February 2017) - Schnider, Armin; Nahum, Louis; Ptak, Radek
Abstract: Behaviourally spontaneous confabulation denotes a distinct syndrome consisting of confabulations that patients act upon, disorientation, and amnesia. It corresponds to the stable form of the original Korsakoff syndrome. While the syndrome may also occur in confusional states and degenerative dementia, this article is about the syndrome as it occurs after acute and focal brain damage. The patients act according to ideas and obligations that can mostly be traced back to real experiences in their past, but which are not currently valid guides of thinking and behaviour. This inability to abandon behavioural guides (anticipations) that are currently not valid corresponds to a failure of behavioural extinction and to the inability to abandon a previously rewarded choice in reversal learning when the expected reward (outcome) fails to occur, that is, following extinction trials. This article describes evidence from human and animal experiments showing that the posterior medial orbitofrontal cortex (OFC), which is typically damaged in these patients, and connected structures of the reward system contain the neural apparatus to signal the non-occurrence of anticipated outcomes, thereby presumably synchronizing thought and behaviour with current reality. Failure of this function, which we call orbitofrontal reality filtering, is associated with behaviourally spontaneous confabulation and disorientation after acute and focal brain damage, but not with other forms of confabulation, and not with reality confusion in degenerative dementia. Potential links with psychosis and decision making will be discussed.